Effect of calcium dose, for the yield of cultivation of vainite (Phaseolus vulgaris), in the district of Barranca. Province of Barranca, Lima region - Legua Cardenas, Jose Antonio (2019)
The present investigation was carried out in Fundo los Anitos, which had as objective to determine the effect of calcium dose, to obtain higher yield of vainite, this started in October 2015, and the treatments were established according to the dose that farmers use, being T1 = 0, 0, T2 = 0, 5, T3 = 0, 75, T4 = 1, 0 l Promet Ca l / 200 l, the application was made at 11, 25, 39 and 53 days. Likewise, the completely randomized block design model was used with four treatments with four blocks and the statistical analysis that was used was in the 1 % and 5 % variance analysis and the Duncan Test at 5 %. Obtained the results it is exposed that the T3 excelled in height of plant with 42, 04 cm, number of flowers with 9, 53 flowers. And also in the laboratory, the diameter of vainite with 1, 01 cm., In length of vainite with 18, 10 cm and weight of a pod with 10, 15 g and in 100 g and in 100 g of dry matter with 2, 80 g of calcium. It also exceeded in greater cost benefit S/ 0, 83